Implementation of a Financial Recording Application for Business Sustainability for MSMEs in the Kota Bambu Selatan District Area, West Jakarta - ROSDIANA, Riska; HERMALA, Irvan; FIRDAUS, Iwan; KARYATUN, Subur (Indonesia Strategic Sustainability, 2024)
Limited understanding and financial recording systems cause MSMEs to experience difficulties in making appropriate financial decisions in running a business and accessing capital credit. In the digital era, understanding technology and innovation is the key to increasing the competitiveness of MSMEs. This community service activity aims for participants to gain an understanding of financial management in the form of simple digital-based planning and recording for MSMEs. Learning outcomes are measured by improving participants' skills in using the digital financial recording application (BukuWarung) to carry out financial bookkeeping and recording. The various features in the BukuWarung financial recording application have the potential to make it easier for MSMEs to prepare their business financial books. The activity implementation method consists of three stages. The first preparation stage includes pre-survey, team formation, making and submitting proposals, coordinating teams and partners as well as preparing materials and training materials. The second stage is the program implementation stage in the form of socialization. Socialization is carried out through counseling (presentation of material) and discussions. The third stage is the evaluation and reporting stage. Evaluation is carried out by comparing the conditions of partners before and after program implementation using the observation method. The training activities were carried out offline in two sessions, namely the first session was lecturing, namely the delivery of training material on the use of digital financial recording applications for MSMEs by resource persons and the second session was discussion, namely discussion activities with the participants.